ZINC THERAPY IN TREATMENT OF ACUTE DIARRHEA IN CHILDREN LESS THAN TWO YEARS (Iraqi Journal of Medical Sciences, 2016)
Background:Diarrhea is the leading cause of morbidity and mortality in children in developing countries, intervention trials showed that using zinc in acute diarrhea decrease morbidity and mortality.Objective:To evaluate the role of zinc supplement in the recovery of hospitalized children with acute diarrhea.Method:The study included one hundred patients presented with acute diarrhea (age 3 months -2 years), forty eight of them were males and fifty two were females, sixty of them were infants and forty were above twelve months. Fifty patients were treated with intravenous fluid only and the other fifty patients were treated with zinc in addition to intravenous fluid.Results:The study showed that the percentage of improvement within the first three days in patients treated with zinc was 80% compared to 44% of control group with P value 0.001. Zn therapy reduce the severity of diarrhea, it is effective in infants but more effective in toddlers, it is similarly effective in both males and females, it is more effective in mixed fed babies than in those on breast or bottle feeding .Using low dose reduce the incidence of vomiting.Conclusion:Zinc therapy is useful in decreasing the duration and severity of acute diarrhea in children.Keywords:Zn (zinc), acute diarrhea.
Keywords: Zn zinc; acute diarrhea